Mainstreaming of Religious Moderation Program in The Department of Islamic Religious Education - Putri, Luqyana Azmiya; Sabarudin; Zebua, Ali Marzuki (Program Studi Pendidikan Agama Islam (PAI), 2023)
Islamic Religious College (PTKI) is a preventive medium in realizing a religious moderation program in which this program is presently carrying an inclusive mission to eradicate the chain of extremism in various lines of religious life. The mainstreaming of religious moderation continues to develop, as evidenced by the incessant movement of universities to implement it. Likewise, IAIN Kerinci, a campus with Islamic nuances in Jambi Province, has also become a pioneer of religious moderation. Various activities that carry the spirit of religious moderation that are often carried out in the Islamic Religious Education department at IAIN Kerinci are a form of real contribution that has been carried out. This study aims to see how far the PAI majors of IAIN Kerinci are in implementing religious moderation programs in the academic community. For this reason, in finding answers, researchers use the field research method, namely field research, to obtain data and information. Data collection techniques include observation, interview, and documentation techniques. The results showed that the PAI department initiated a religious moderation program that started from the literacy ground and then began to touch on various academic activities.